Multiple transcription factors involved in the response of Chinese cabbage against Plasmodiophora brassicae - Meng, Sida; Yan, Xinyu; Piao, Yinglan; Li, Shizhen; Wang, Xin; Jiang, Jing; Liang, Yue; Pang, Wenxing (Frontiers in Plant Science, 2024)
Clubroot disease, which is caused by the obligate biotrophic protist Plasmodiophora brassicae, leads to the formation of galls, commonly known as pathogen-induced tumors, on the roots of infected plants. The identification of crucial regulators of host tumor formation is essential to unravel the mechanisms underlying the proliferation and differentiation of P. brassicae within plant cells. To gain insight into this process, transcriptomic analysis was conducted to identify key genes associated with both primary and secondary infection of P. brassicae in Chinese cabbage. Our results demonstrate that the k-means clustering of subclass 1, which exhibited specific trends, was closely linked to the infection process of P. brassicae. Of the 1610 differentially expressed genes (DEGs) annotated in subclass 1, 782 were identified as transcription factors belonging to 49 transcription factor families, including bHLH, B3, NAC, MYB_related, WRKY, bZIP, C2H2, and ERF. In the primary infection, several genes, including the predicted Brassica rapa probable pectate lyase, RPM1-interacting protein 4-like, L-type lectin-domain-containing receptor kinase, G-type lectin S-receptor-like serine, B. rapa photosystem II 22 kDa protein, and MLP-like protein, showed significant upregulation. In the secondary infection stage, 45 of 50 overlapping DEGs were upregulated. These upregulated DEGs included the predicted B. rapa endoglucanase, long-chain acyl-CoA synthetase, WRKY transcription factor, NAC domain-containing protein, cell division control protein, auxin-induced protein, and protein variation in compound-triggered root growth response-like and xyloglucan glycosyltransferases. In both the primary and secondary infection stages, the DEGs were predicted to be Brassica rapa putative disease resistance proteins, L-type lectin domain-containing receptor kinases, ferredoxin-NADP reductases, 1-aminocyclopropane-1-carboxylate synthases, histone deacetylases, UDP-glycosyltransferases, putative glycerol-3-phosphate transporters, and chlorophyll a-binding proteins, which are closely associated with plant defense responses, biosynthetic processes, carbohydrate transport, and photosynthesis. This study revealed the pivotal role of transcription factors in the initiation of infection and establishment of intracellular parasitic relationships during the primary infection stage, as well as the proliferation and differentiation of the pathogen within the host cell during the secondary infection stage.